Effect of acute fatigue and training adaptation on countermovement jump performance in elite snowboard cross athletes - Gathercole, R. J.; Stellingwerff, T.; Sporer, B. C. (The Journal of Strength and Conditioning Research, 2015)
Countermovement jump performance was examined in response to acute neuromuscular (NM) fatigue (study I) and chronic training (study II) in elite snowboard cross (SBX) athletes, through both typical (countermovement jump [CMJ]-TYP) and alternative (CMJ-ALT) CMJ variables. Seven (4 men and 3 women) elite (Olympic-level) SBX athletes participated in study I, and 5 of the same athletes (2 men and 3 women) participated in study II. Countermovement jump variables relating to force, velocity, power, and time were measured during both eccentric and concentric jump phases, with CMJ-TYP variables reflecting CMJ output and CMJ-ALT variables reflecting CMJ mechanics. In study I, CMJ performance was assessed before and after a fatiguing lower-body exercise protocol, and in study II, CMJ performance was examined before and after a 19-week structured training block. Meaningful differences in CMJ performance were examined using the magnitude of change (effect sizes [ES]) for group and individual changes. Acute fatigue decreased peak force and eccentric function, while the duration of the jump increased. The structured training block increased peak force and eccentric function, while jump duration markedly decreased. In both study I and study II, the largest ES were associated with CMJ-ALT variables. The CMJ test seems a suitable monitoring tool in elite SBX athletes for the detection of both acute fatigue and training-adaptation. Compared with CMJ output, CMJ mechanics exhibits more marked and divergent changes after both acute NM fatigue and a structured training block. CMJ-ALT variables should therefore be incorporated into CMJ analysis.